Determination of molecular weight of genomic RNA of a virulent rinderpest virus and comparison of wavelength scans of extraceIhdar viruses and intracellular nucleocapsids of virulent isolates and attenuated strains* - Rattan, B; Sharma, B; Bansal, R P (The Indian Journal of Animal Sciences, 2012)
The molecular weight of genomic RNA of virulent 'Hisar' isolate of rinderpest virus (RPV) was determined by electrophoretic analysis under fully denaturing conditions, it corresponded to 47S. The wavelength scans of density gradient of purified extracellular viruses and intracellular nucleocapsids of two virulent isolates ('Hisar' and 'Bangalore') and two attenuated strains (RBOK and lapinised) were compared, no differences were observed within or between virulent isolates and attenuated strains in this property.